Quand les héritiers deviennent des « entrepreneurs » : les nouveaux appuis rhétoriques et pratiques de l’accumulation - Camille Herlin-Giret (Revue de la Régulation)
Assets financialisation isn’t new. But the advent of financial holdings has recomposed wealthy people morphology. These transformations blur common divisions - labor and capital, private and professional wealth, inheritance and recent fortunes - which have yet been echoed by the success of an entrepreneurial rhetoric. The latter provides a robust legitimation to wealth accumulation by building two separates figures: the rich annuitant and the wealthy entrepreneur. The paper underlines that transformations of wealthy people are difficult to capture, especially because the state has hidden these new ways of ownership.